Humanitarian paradigms and their peculiarities - Afanasiev, Oleksandr (Actual Problems of Mind, 2017)
The paper analyses some peculiarities of humanitarian paradigms by comparison with the paradigms in science. The author proposes to distinguish four main senses of the term «humanitarian paradigm» which is not identical with the term «paradigm in the humanities».